Repeated maternal separation: Alcohol consumption, anxious behavior and corticosterone were reversed by a non-pharmacological treatment - Odeon, Maria Mercedes; Acosta, Gabriela Beatriz (Elsevier, 2020)
Adverse events in early life have been related to a maladaptive stress response during adulthood, which could predispose individuals to psychiatric and physiological disorders. The purpose of this work was to study the implications of repeated maternal separation (RMS) plus a physical stressor (cold stress), voluntary ethanol consumption and plasmatic levels of corticosterone (Cor) via conflict behavior tests. To this aim, pups were separated daily from their mothers for one hour and subjected to cold stress (4 °C) between postnatal days (PD) 2 and 20. Control groups were left undisturbed with their mothers. Afterwards, all groups were exposed to voluntary ethanol (6%) or dextrose (1%) intake for 7 days. After a 30-day period of environmental enrichment (EE), the animals were again exposed to the voluntary intake protocol for 7 days. At 66 days, they were subjected to different conflict tests. Thereafter, rats were sacrificed by decapitation and blood trunk was collected to determine plasma corticosterone levels. We demonstrated that early RMS increased both voluntary alcohol intake and Cor levels. Moreover, young adult animals showed excessive activity in conflict tests. Whereas in animals exposed to a non-pharmacological treatment, known as environmental enrichment (EE), the effects previously obtained were reversed and/or prevented. In summary, we can conclude that the combination of maternal separation in early life plus cold stress increase both the voluntary exposure to alcohol and disruptive behaviors. This is a risk factor for the development of chronic diseases such as alcoholism and long-term depression. However, we found that an enriched environment may have a beneficial effect with respect to alcohol intake and aggressive behaviors.